Level Of Impact On Factors Governing Time Overrun In Construction Projects (International Journal of Environmental Sciences, 2025)
Construction companies focus on mitigating time overrun in construction projects. Time overrun is one of the major constraints faced by the construction industry. Conversely, time overrun prevails in all stages of the construction process and thereby augments the project total period (Yang and Ou, 2008). In rare cases, the projects are completed on time (Assaf and AlHejji, 2006) [2], and henceforth it is necessary to pay stern attention to managing time in construction projects as delay in each and every day adds to a significant sum of revenue which is barely recovered. Therefore, researchers have started to investigate the factors affecting time overrun in construction projects across different countries and cities. In Indonesia, factors such as changes in design, insufficient planning, deprived labour productivity, and shortage of resources influence time overrun in high-rise buildings (Kaming et al., 1997) [5]. Considering the time overrun factors and its impact, it is need to pay attention focusing on the major factors that have a high influence on construction projects.